2014
DOI: 10.18632/oncotarget.3064
|View full text |Cite
|
Sign up to set email alerts
|

Genistein suppresses FLT4 and inhibits human colorectal cancer metastasis

Abstract: Dietary consumption of genistein, found in soy, has been associated with a potentially protective role in colorectal cancer (CRC) development and progression. Herein we demonstrate that genistein will inhibit human CRC cell invasion and migration, that it does so at non-cytotoxic concentrations and we demonstrate this in multiple human CRC cell lines. After orthotopic implantation of human CRC tumors into mice, oral genistein did not inhibit tumor growth, but did inhibit distant metastasis formation, and was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…These effects were completely antagonized by ERs antagonist fulvestrant (Schleipen et al, 2011). In mice implanted with human colorectal cancer tumors, orally administered genistein did not inhibit tumor growth, but it did inhibit distant metastasis formation, and displayed no toxicity (Xiao et al, 2014). Apigenin and naringenin showed to be effective in the reduction of ER-mediated cell growth in non-malignant young adult mouse colonocytes (YAMC) and, interestingly, when administered in combination, they showed a strong enhanced activity with significantly lower concentration compared to the single administration (Yang et al, 2014).…”
Section: Natural Xenoestrogensmentioning
confidence: 99%
“…These effects were completely antagonized by ERs antagonist fulvestrant (Schleipen et al, 2011). In mice implanted with human colorectal cancer tumors, orally administered genistein did not inhibit tumor growth, but it did inhibit distant metastasis formation, and displayed no toxicity (Xiao et al, 2014). Apigenin and naringenin showed to be effective in the reduction of ER-mediated cell growth in non-malignant young adult mouse colonocytes (YAMC) and, interestingly, when administered in combination, they showed a strong enhanced activity with significantly lower concentration compared to the single administration (Yang et al, 2014).…”
Section: Natural Xenoestrogensmentioning
confidence: 99%
“…Genistein, a natural phytoestrogen found in soy, has demonstrated the potential to inhibit numerous types of cancer, including breast, pancreatic and colorectal cancers (13)(14)(15). Previous studies have indicated that this effect may be due to its ability to induce cancer cell apoptosis, arrest the cell cycle and inactivate critical signaling pathways in human cancer cells (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The validation on orthotopic mice models, of colorectal tumours, the genistein treatment (oral delivery) did not significantly reduced tumour growth, but was able to prevent distant metastasis [110]. In oral cancer the antimetastatic effect was related by regulating the MMP-2 expression by inhibition of ERK1/2 and the activator protein-1 signalling pathways [111].…”
Section: Phytochemical Compounds and Cancermentioning
confidence: 99%